1980
DOI: 10.1159/000250460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyproterone Acetate Orally on Hair Density and Diameter and Endocrine Factors in Women with Idiopathic Hirsutism

Abstract: The effect of oral cyproterone acetate on hair density and diameter was studied in a clinically homogeneous group of 11 women with idiopathic hirsutism. Therapy was continued for 12 cycles of treatment. Hair density and mean hair diameter on the chin and left upper leg were measured before, immediately after and 3 months after therapy. Generally, the effect of treatment consisted of a quantitative reduction of both parameters, but the effect was not permanent after termination of therapy. Concurrently, the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…52 Reasonably, treatment of hirsutism with the antiandrogen cyproterone acetate leads to significant reduction of hairiness. [57][58][59][60][61] Treatment with other antiandrogenic hormones or drugs for hirsutism has also been promising. 47,48 Androgens, however, show an entirely opposite effect on the scalp hair follicles.…”
Section: Androgen Action On Hair Growthmentioning
confidence: 99%
“…52 Reasonably, treatment of hirsutism with the antiandrogen cyproterone acetate leads to significant reduction of hairiness. [57][58][59][60][61] Treatment with other antiandrogenic hormones or drugs for hirsutism has also been promising. 47,48 Androgens, however, show an entirely opposite effect on the scalp hair follicles.…”
Section: Androgen Action On Hair Growthmentioning
confidence: 99%
“…The effects of CA on plasma testosterone levels has also to be clarified. Peereboom-Wynia et al 18) could find no correlation between the degree of hirsutism, the concentration of plasma testosterone, dehydroepiandrosterone sulphate and androstenedione before and after treatment. Tejero et al 19) however showed a significant reduction in the plasma testosterone levels in CA treated women who had raised pre-treatment levels.…”
Section: Discussionmentioning
confidence: 90%
“…They reported that the hirsutism score fell by 50% over 6 months, although in reporting their results the investigators did not differentiate between women with IH and PCOS. Peereboom-Wynia and Boekhorst (151) treated another 11 well defined women with IH using CPA,100 -200 mg, on days 5-15 and EE, 50 g, on days 5-26 of the cycle, and reported a reduction in the hair density and diameter (151). Overall, it would appear that CPA is effective in treating patients with IH, although larger studies are still lacking.…”
mentioning
confidence: 99%